Study on Preparation and Wear Resistance of Aluminum Nitride (AlN)Coating on the Surface of ADC12 Aluminum Alloy - DING Shanlin, WANG Jiangying, ZHANG Ying, HU Lijun (Cailiao Baohu, 2023)
In order to improve the wear resistance of ADC12 aluminum alloy material，a multi-functional ion nitriding furnace was used to perform ion nitriding on the surface of ADC12 aluminum alloy to prepare aluminum nitride (AlN) coatings.The phase structure and micro-morphology of AlN coating were characterized by X-ray diffraction and scanning electron microscope.The adhesion between AlN coating and substrate，friction coefficient，specific wear rate and friction and wear mechanism were studied by WS-2005 coating adhesion automatic scratch tester，WTM-2E controlled atmosphere micro friction and wear tester and 3D optical microscope.Results showed that the phase structure of AlN coating was face-centered cubic，and no diffraction peak of Al2O3was found.With the increase of nitriding temperature and nitriding time，the thickness of AlN coating gradually increased，the film-based adhesion of AlN coatings increased first and then decreased；Under the condition of nitriding at 510 ℃for 4 h，the optimum adhesion of the film base was 56.60 N.Compared to the matrix，after the conducting friction and wear tests for 10 minutes under loading 1 N，the friction coefficient and specific wear rate of AlN coating samples decreased.The thicker the surface AlN coating，the more significant the wear reduction effect were.The aluminum nitride (AlN) coating obtained from ion nitriding on the surface of ADC12 aluminum alloy had excellent wear resistance.